Moving Nigerian forestry forward through urban forestry development: Lessons from the United States experience (2006)
This paper examined the potential o f urban forestry development in the overall development of forestry in Nigeria. It showed how urban forestry succeeded in shooting forestry into greater prominence and therefore greater achievements in the United States. The roles of prominent actors such as the professional and citizen organizations, the public, media, politicians, government functionaries and the academia in urban forestry development were investigated. Lessons learnt from the United States experience include placing a challenge on the Forestry Association o f Nigeria to spearhead the formation o f urban forestry movement in Nigeria, setting up o f national urban forestry working group, organising regional technical seminars and conferences on urban forestry as well as expanding forestry curricula to accommodate changing demands o f managing trees in the modern urban environment. The study concludes by recommending the immediate setting up of National Urban Forestry Working Group to start putting together in earnest the blueprint for urban forestry development in Nigeria.